Spiritul critic, trăsătură esențială a portretisticii lui Nicolae Iorga - Lucian Chișu (Revista de Istorie și Teorie Literară)
Encyclopaedist-historian of the entire Romanian culture, initiator of the literary trend known as „Semănătorism”, editor of newspapers and author of several Histories of Romanian literature, poet, pamphleteer, essayist, dramatist and memorialist, Nicolae Iorga was a first-rate personality in all these fields. The diversity of his pursuits makes it difficult to separate these spheres of activity, which intertwine, more than once. Among the most relevant interferences detected in his work are the portraits of his contemporaries, published by Iorga in press and, later, preserved in edited pages, one of the most well-known and read books of Nicolae Iorga having the title People who were (4 vols.). The present article aims to comment on the presence of these portraits in the two types of writing, journalistic and literary-artistic, delimiting them according to the work criteria of each field and trying to explain their cohabitation in the written press of the last century. The conclusion is that this fact was possible due to the engaged journalism of the French press. This „format” was adopted and practiced by the luminaries of our nascent journalism in the first decades of the 19th century, a model perpetuated for a long time by the massive involvement of the cultural figures in the journalistic phenomenon, a presence diminished today to the point of extinction.